Synthesis of cyclobutane analogues - Yan Bai Yin; Zhan Qian Song; Zong De Wang; Shi Bin Shang; Zhao Sheng Cai (Bulletin of the Chemical Society of Ethiopia, 2009)
2-(3-Acetyl-2,2-dimethylcyclobutyl)acetic acid (pinonic acid) was synthesized using α-pinene as raw material and potassium permanganate as oxidant. This compound reacted with substituted aniline to produce eight kinds of derivatives with cyclobutane moiety. The yields of the cyclobutane analogues ranged from 24.9 to 78.2 %.